2022
DOI: 10.1002/adfm.202110992
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Elemental Modulation on Phase Purity and Electrochemical Properties of Co‐free High‐Entropy Spinel Oxide Anodes for Lithium‐Ion Batteries

Abstract: High entropy oxide (HEO) is a new class of lithium-ion battery anode with high specific capacity and excellent cyclability. The beauty of HEO lies in the unique tailorable properties with respect to tunable chemical composition, which enables the use of infinite element combinations to develop new electrode materials. This study synthesizes a series of Co-free spinel-type HEOs via a facile hydrothermal method. Based on quaternary medium-entropy (CrNiMnFe) 3 O 4 , the fifth elements of V, Mg, and Cu are added, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(41 citation statements)
references
References 71 publications
2
34
0
Order By: Relevance
“…The materials show significantly enhanced solubility limits and excellent structural stability, with most of the exceptional properties emerging from synergistic effects, beyond a simple rule of mixing. , When the HEO-based anodes are compared, all have one thing in common: regardless of the synthesis method and resulting morphology, they always exhibit remarkable cycling stability, which distinguishes them from conventional analogues. The observed excellent cycling performance of HEOs is attributed, at least to some degree, to the influence of the high entropy on the phase stabilization. , ,,, However, until now, it has not been properly addressed how exactly the entropy can stabilize phases in the ongoing electrochemical process, which leads to a decomposition of the initial structure. The current state of knowledge on the electrochemical working mechanisms of HEOs is summarized in Supplementary Note 2.…”
Section: Introductionmentioning
confidence: 99%
“…The materials show significantly enhanced solubility limits and excellent structural stability, with most of the exceptional properties emerging from synergistic effects, beyond a simple rule of mixing. , When the HEO-based anodes are compared, all have one thing in common: regardless of the synthesis method and resulting morphology, they always exhibit remarkable cycling stability, which distinguishes them from conventional analogues. The observed excellent cycling performance of HEOs is attributed, at least to some degree, to the influence of the high entropy on the phase stabilization. , ,,, However, until now, it has not been properly addressed how exactly the entropy can stabilize phases in the ongoing electrochemical process, which leads to a decomposition of the initial structure. The current state of knowledge on the electrochemical working mechanisms of HEOs is summarized in Supplementary Note 2.…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al 46 observed that Cu and Ni were hardly reoxidized upon first charging ([FeCuNiCrMn] 3 O 4 -based half cell), which is anomalous in known HEOs since they are usually regarded as active elements. Sun et al 47 and Patra et al 48 found that S-HEO undergoes a spinel to rock salt transformation in the first half-cycle, and the two phases coexist in subsequent reactions. This finding seems to run contrary to the single-phase retention capability of HEO.…”
Section: Electrochemical Mechanismmentioning
confidence: 99%
“…To date, many research groups have synthesized high-entropy oxides as electrode materials for LIBs that show good performance and great cycling stability, but the rigorous synthesis conditions, high cost, and cumbersome process greatly hinder their development and applications. [27][28][29] Moreover, it is known that material properties have a strong structural dependence. Structure regulation is one of the most effective means to construct more active sites to improve properties and thus enhance performance.…”
Section: Introductionmentioning
confidence: 99%
“…To date, many research groups have synthesized high-entropy oxides as electrode materials for LIBs that show good performance and great cycling stability, but the rigorous synthesis conditions, high cost, and cumbersome process greatly hinder their development and applications. 27–29…”
Section: Introductionmentioning
confidence: 99%